Diversity of benthic diatoms and water quality of the Ping river, Northern Thailand - Pongpan Leelahakriengkrai (2018)
A study on the diversity of benthic diatoms and water quality of the Ping River, Northern Thailand were carried out from December 2004-December 2005. Samples were collected from 15 sites covering the whole river. The water quality was based on specific physical and chemical factors indicated the water in the Ping River was moderately clean and classified in the mesotrophic status, except in the upstream area which was clean to moderate and of the oligo-mesotrophic status. Changing in water quality depended on the environmental status surrounding the sampling sites and seasonal changes. Two orders, forty genera and one hundred and twenty eight species of benthic diatoms were found and classified into the Division Bacillariophyta. Most of them (97%) were pennate diatoms in the Order Bacillariales. The remaining 3% were centric diatoms in the Order Biddulphiales. The relationship between water quality and dominant benthic diatoms in each sampling site and season were determined. It was found that Nitzschia palea (Kützing) W. smith, Nitzschia sp. 2 and Synedra ulna var. aequalis (Kützing) Hustedt were indicator species for moderate water quality whilst Cymbella turgidula Grunow, Gomphonema lagenula K̈tzing and Navicula symmetrica Patrick were indicator species of clean to moderate water quality.